The detection of Cryptosporidium serpentis in snake fecal samples by real-time PCR - Silva, Deuvania C. da [UNESP]; Paiva, Philipp Ricardo S. O.; Nakamura, Alex Akira [UNESP]; Homem, Camila Guariz [UNESP]; Souza, Milena Sato de [UNESP]; Grego, Kathleen Fernandes; Meireles, Marcelo Vasconcelos [UNESP] (Elsevier B.V., 2014)
Infection by Cryptosporidium serpentis occurs in reptiles, particularly in snakes. This disease is characterized by chronic infection with the presence of hypertrophic gastritis. The objectives of this study were to use real-time polymerase chain reaction (PCR) targeting the heat shock protein 70 (Hsp70) gene for the detection of C serpentis in fecal samples from snakes and to determine the analytical and epidemiological specificity and sensitivity of this approach relative to the gold standard of nested PCR for the amplification of a fragment of the 18S subunit of the ribosomal RNA (18S rRNA) gene followed by the sequencing of amplified fragments (nPCR/S). Individual fecal samples were collected on a single occasion from 503 asymptomatic adult snakes housed in the serpentarium of the Butantan Institute in Sao Paulo, Brazil. The nested PCR revealed that 60 samples (11.98%) were positive for Cryptosporidium sp. The sequencing of amplified fragments, which was possible for 38 samples, resulted in the identification of Cryptosporidium tyzzeri (7), Cryptosporidium muris (4), Cryptosporidium varanii (12) and C sementis (15) in fecal samples from several snake species. The real-time PCR approach indicated that 17 samples (3.37%) were positive for C. serpentis, whereas the nPCR/S indicated that 15 samples (2.98%) were positive for C. serpentis. The epidemiological sensitivity and specificity of real-time PCR were 93.8% and 99.5%, respectively. Thus, we conclude that real-time PCR targeting the Hsp70 gene is a sensitive and specific method for the detection of C. serpentis in snake fecal samples. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Epidemiology; Cryptosporidium; Reptiles; Molecular diagnosis